Human Excreta as a Stable and Important Source of Atmospheric Ammonia in the Megacity of Shanghai. - Yunhua Chang; Congrui Deng; Anthony J Dore; Guoshun Zhuang (PLoS ONE)
Although human excreta as a NH3 source has been recognized globally, this source has never been quantitatively determined in cities, hampering efforts to fully assess the causes of urban air pollution. In the present study, the exhausts of 15 ceiling ducts from collecting septic tanks in 13 buildings with 6 function types were selected to quantify NH3 emission rates in the megacity of Shanghai. As a comparison, the ambient NH3 concentrations across Shanghai were also measured at 13 atmospheric monitoring sites. The concentrations of NH3 in the ceiling ducts (2809(-2661)(+5803) μg m(-3)) outweigh those of the open air (~10 μg m(-3)) by 2-3 orders of magnitude, and there is no significant difference between different seasons. δ15N values of NH3 emitted from two ceiling ducts are also seasonally consistent, suggesting that human excreta may be a stable source of NH3 in urban areas. The NH3 concentration levels were variable and dependent on the different building types and the level of human activity. NH3 emission rates of the six residential buildings (RBNH3) were in agreement with each other. Taking occupation time into account, we confined the range of the average NH3 emission factor for human excreta to be 2-4 times (with the best estimate of 3 times) of the averaged RBNH3 of 66.0±58.9 g NH3 capita(-1) yr(-1). With this emission factor, the population of ~21 million people living in the urban areas of Shanghai annually emitted approximately 1386 Mg NH3, which corresponds to over 11.4% of the total NH3 emissions in the Shanghai urban areas. The spatial distribution of NH3 emissions from human excreta based on population data was calculated for the city of Shanghai at a high-resolution (100×100 m). Our results demonstrate that human excreta should be included in official ammonia emission inventories.